Sarojini Naidu Poem's Themes: Love Life And Death: The Significance of Human Values in Education (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Human values are the morals that characterize or give significance to our lives. Schooling isdeficient on the off chance that we overlook the part played by such values. There are scores of values yetthe ten most significant human values organized in the request for their significance are-Co-activity,Caring, Honesty, Love, Respect, Faith, Beauty, Trust, Integrity, and Wisdom. The capacity of training is tomake ideal citizens. Training is a process which molds the person and personality of a person.Furthermore, a holistic climax is accomplished just when this training is fused with human values. In theevent that human values or morals are instructed through the means of lectures, the goal wouldn't besatisfied. It will result in a disappointment. Then again it is a deeply grounded truth that anything whichis instructed in an engaging way can never be neglected, and it shall remain perpetually in the memoryof the beneficiary.